ECONOMIC LOSSES DUE TO CONDEMNATION OF SWINE ORGANS IN SLAUGHTERHOUSES UNDER MUNICIPAL INSPECTION SERVICE - Fruet, Ana Paula Burin; Scortegagna, Análie; Fabricio, Edom de Avila; Kirinus, Jackeline Karsten; Dörr, Andréa Cristina; Nörnberg, José Laerte (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611708727 This study aimed to measure the economic losses caused by the condemnation of swine organs in municipal slaughterhouses under the supervision of the municipal inspection system (MIS) from the city of Santa Maria-RS during 12 months in a row. The study was conducted by collecting data from slaughterhouses in Santa Maria, Rio Grande do Sul, Brazil, in MIS. The registered data took into account the number of animals slaughtered, number of condemned organs and major lesions that led to condemnation from October 2010 to September 2011. During the evaluation period, 6,193 animals were slaughtered. It was found that 5,511 organs were condemned, mostly because of aspiration of blood (n = 1,231), larval migration in liver (n = 991), and renal cyst (n = 807). The survey revealed that R$ 11,955.66 is wasted annually in condemnation of organs. It is noteworthy that the main injury that contributed to the economic damage was larval migration in liver, which discard amount reached R$ 8,919.00. In order to reduce economic losses, it is necessary to do something against the critical points of condemnation, in which the main one observed in the study was the disposal of liver caused by larval migration.